2019
DOI: 10.1016/j.fuel.2019.01.170
|View full text |Cite
|
Sign up to set email alerts
|

The Heat Treatment Severity Index: A new metric correlated to the properties of biochars obtained from entrained flow pyrolysis of biomass

Abstract: The properties of biochars produced in biomass pyrolysis processes highly depend on the pyrolysis conditions, specifically the pyrolysis temperature and thermal treatment duration. The higher the temperature and the duration, the more severe is the heat treatment. The present work proposes a new Heat Treatment Severity Index (HTSI) for the quantification of the heat treatment severity during the pyrolysis reaction. This metric takes into account both effects of reactor temperature and heat treatment time insid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 41 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…It is worth noting that the ash content in the DBC feedstock was lower than that in bamboo, based on Hernandez-Mena et al [ 42 ] (2.57%), Wang et al [ 37 ] (2.10%), and Sahoo et al [ 36 ] (1.58%). The FC content in woody biomass varies depending on plant type; therefore, the FC of DBC was 10.24% different from that of other wooden feedstocks, such as 15.2% for beech wood [ 49 ], 35% of tree bark (Pinus pinaster), and 19% of applewood [ 45 ] .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth noting that the ash content in the DBC feedstock was lower than that in bamboo, based on Hernandez-Mena et al [ 42 ] (2.57%), Wang et al [ 37 ] (2.10%), and Sahoo et al [ 36 ] (1.58%). The FC content in woody biomass varies depending on plant type; therefore, the FC of DBC was 10.24% different from that of other wooden feedstocks, such as 15.2% for beech wood [ 49 ], 35% of tree bark (Pinus pinaster), and 19% of applewood [ 45 ] .…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that with increasing temperature, the DBC biochar had progressively higher C content, resulting from the removal of dissociated bonds between C and functional groups on the surface of the biomass, including –OH, aliphatic C–O, and aliphatic C–H groups [ 9 , 19 , 33 , 47 ]. The aromatization process begins at approximately 350 °C and continues at higher temperatures [ 40 , 49 ]. The aromatic C–H deformation increased until the temperature reached 500 °C [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the various types of feedstocks and the complexity of the production process, designing a suitable pyrolysis process to control the excellent quality of biochar is challenging [11,39]. Typically, biochar quality is strongly influenced by temperature and holding time and is determined by the C content and the atomic ratios of H/C, O/C, and (O+N)/C, representing the degree of carbonization, aromaticity, polarity, and stability of biochar, respectively [11,57].…”
Section: Suitable Pyrolysis Conditions For Producing High-quality Bio...mentioning
confidence: 99%
“…Although many pyrolysis conditions can affect biochar properties, a meta-analysis of the literature performed by Ippolito et al [37], Wang et al [38], and Guizani et al [39] showed that temperature and holding times are considered strong factors that directly influence biochar properties, the breakdown of lignocellulosic feedstocks and chemical bonds, and the physical and chemical structure of the resultant biochar [32,40,41]. A comprehensive review of the literature on biochar shows that the properties of biomass feedstocks change with the techniques and conditions employed in the pyrolysis process [42][43][44].…”
Section: Introductionmentioning
confidence: 99%